Inequality, disinterest and mistrust: abstention in the legislative elections of 1999 - C. Magalhães, Pedro (2001)
The analysis of the abstention in the legislative elections of 1999 reveals an approximation to the pattern common to the majority of occidental democracies: the absence of a direct impact on individuals' economic and educational resources and a considerable age and family isolation effect on electoral participation. However, what was more important was the impact of political attitudes. The abstention in 1999 was a socially diffuse phenomenon, but concentrated among electors who share attitudes that are generally seen as stable and enduring: non-party membership and mistrust of the political system.